Design Of Karo Traditional Virtual Museum In Medan City (International Journal of Architecture and Urbanism, 2024)
One of the biggest cities in Indonesia is Medan, which serves as the provincial capital of North Sumatra and is growing pretty quickly. There are many different cultures ingrained in the city of Medan itself. The several varied tribes who call the city home demonstrate this. In Indonesia, diversity and cultural distinctions are highly valued. As a result, it is imperative to conserve the artistic traditions of the many ethnic groups that make up Medan. A museum is, broadly speaking, an organization or non-profit that works to educate and serve the public. Its open-minded approach is used in the gathering, preservation, study, sharing, and public display of actual and virtual artifacts for educational purposes. both learning and enjoyment. A museum's primary purpose is to gather, preserve, and periodically display artifacts for the general public or select guests. The primary issue is that there is now no Karo Museum in Medan City, despite the fact that it is one of the biggest cities in Indonesia and was founded by a member of the Karo Tribe. Consequently, it is anticipated that the layout of the Karo Traditional Virtual Museum would offer more thorough historical details regarding the history of Medan City and the Karo Culture.